THE ROLE OF LANGUAGE IN THE FORMATION OF EMOTIONS (Conferencea, 2022)
This article presents the relationship between language and emotion, the history of the study of emotions and examples of research work. Separate definitions have been collected for the term emotion. In this regard, samples of studies conducted in psychology and linguistics are compared, their differences and similarities are discussed in detail.